Gender equity in education: Helping the boys catch up - Vicente B. Paqueo; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2019)
The article argues that in the Philippines there is a need for a more nuanced view of gender equality. Historically, Filipino males were somewhat more educated than females. Now the males are lagging behind the females and the education gender gap is widening. This reversal was predictable early on in the 70s before it manifested itself in national statistics. The paper argues that today gender equality advocacy should go beyond the stereo-typical focus on girls' education and pay more attention to issues that are hurting boys' education. Failure to pursue win-win strategies to address gender bias in education working against boys will mean the country is foregoing valuable opportunities to raise equity and economic returns to its investment in education. To conclude, the paper suggests some experiments to deepen current understanding of boys' educational issues and develop tools for effectively removing existing impediments to schooling and learning.
Keywords: 330; gender equity; education; Philippines